The Relationship Between Literature and History Through Hypertextuality in Ruperta Bautista’s ‘Ixbalam-ek ‘ - Guzman Palomeque, Itzel (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
This article seeks to explore the link between literature and history in contemporary indigenous literature, with the novel Ixbalam-ek ‘ by the Tsotsil author Ruperta Bautista, through Gerald Genette’s theory of hypertextuality. It is intended to demonstrate, by means of four of the seven categories that integrate hypertextuality, how the novel presents a connection with ancient Mayan texts such as the Popol Vuh and the Chilam Balam.